On the theory of one-sided models in spaces with arbitrary cones. (1990) - Martynyuk, A. A.; Obolensky, A. Yu.
Abstract : The paper presents a way of constructing quasimonotone nonautonomous systems ensuring x -stability of the nonautonomous system. There are described extensions quasimonotone with respect to an arbitrary cone, Perron condition and invariant surface stability under perturbations U -stability on the set of non wandering points is proved to imply u -stability of quasimonotone nonlinear system and exponential u -stability on minimal attraction center provides u -stability of the total systems Examples are available.